A autorregulação da destinação final dos resíduos nanotecnológicos: a possibilidade de utilização do protocolo da OECD e do pluralismo jurídico (Teubner) para Gestão do Risco do Nanowaste - Leal, Daniele Weber da Silva (Universidade do Vale do Rio dos Sinos, 2017)
Currently it’s faced the challenge of new demands arising from the nanotechnology’s complexities era are. They are various products at nano scale, spread by society in all areas, such as cosmetics, medicine, engineering, civil construction, environmental remediation, among many others. However, in parallel with the beneficial promises, there is (potential) risk. This facet is permeated by doubts, scientific uncertainties about the possible nano impacts on human life and the environment. Its effects on the ecosystem, so far, have not had concrete effects. Shown are dismay before imagined, given the particularities of the nano scale and its interaction with the ecosystem. Given the growing industrial production of nanotechnologies, and widespread use in society, there is a new concern: nanotechnology wastes, or nanowaste. The higher the circulation of nanoproducts, the greater the disposal at the end of the useful life of nanomaterials. Still in the context of risk, how could nanowaste get an adequate final disposal? An answer to this question will be found in the life cycle analysis of nanomaterials, together with the specific study carried out by the OECD, on the management of nanotechnological wastes, illuminated by the principles of the Precautionary Principle. There are no regulatory specific frameworks to nanotechnologies, nor about nanowaste. Therefore, this research aims to demonstrate how the specific protocol on nanotechnology residues of the OECD, located in a prominent international space, could be adopted as a self-regulatory instrument in order to regulate the final destination of nanowaste as risk management, in a space illuminated by the precautionary principle. The systemic-constructivist methodology, combined with the data analysis in the OECD data collection, will be used. In this context, such as the structuring of the elements of Legal Pluralism proposed by Gunther Teubner, together with the pools of responsibility (also in dialogue with Luhmann's communication), may help to model an instrument of self-regulation, permeated by the precautionary principle, specific to the OECD? Adopting and validating the OECD instrument, as a self-regulation measure, a true management of the nanowaste will be possible, using minimal mechanisms in the final disposal and treatment of waste, protecting the environment and human life, respecting the precaution, and also as a measure of responsible development for the nanotechnology era.
Keywords: Nanotecnologias; Risco; Nanowaste; Autorregulação; Gestão de resíduos; Destinação final; Pluralismo jurídico; Protocolo da OECD; Nanotechnologies; Risk; Nanowaste; Self-regulation; Final disposal; Legal pluralism; OECD’s protocol; Waste management; ACCNPQ::Ciências Sociais Aplicadas::Direito